Juridical Analysis of the Refusal of Home Emptying Post-Sale by Seller (Study of Decision Number 626/PDT.G/2019/PN.MDN) - Siregar, M. Ricky Andriansyah; Sembiring, Rosnidar; Sutiarnoto; Abd. Harris (International Journal of Economic, Technology and Social Sciences (Injects), 2024)
The purpose of this study is to find out the applicable legal mechanism related to the emptying of houses after sale by sellers; to analyze and find out the process of resolving legal disputes that can be applied in cases of refusal to vacate the house after sale by the seller; and to analyze and find out the analysis in the judge’s consideration of the court decision number 626/Pdt.G/2019/PN.Mdn. The results of the study show that the existence of an agreement to vacate the house in the sale and purchase deed reduces the risk of refusal to vacate the house by the seller; The results of this study show that out-of-court settlement or non-litigation is an important way to resolve this house vacancy case, because it is faster, more efficient and effective, for example, the parties can choose what kind of non-litigation dispute resolution must be carried out in order to obtain justice and legal certainty. Juridical levering guarantees that the legal ownership rights are transferred from the seller to the buyer in accordance with the applicable legal provisions, as mentioned in article 1457 of the Civil Code and 1458 of the Civil Code and there is a discrepancy in the rules of civil procedure law where in the decision the defendant I and defendant II are not present in the trial where in article 125 Paragraph (1) which is often called the verstek decision, namely all lawsuits from the plaintiff must be granted, However, in the judge’s decision above, the lawsuit from the plaintiff was only partially accepted, in the judge’s consideration it was also not mentioned that the object of the case was not confiscated through the court and there was no coercive effort by the court against the emptying of the object of the case, which resulted in losses by the plaintiff.